The Effect of Green Finance, Green Energy, and ESG Performance on Carbon Neutrality: Empirical Study on Energy Sector Companies in Indonesia - Namora Safira Siregar; Murtanto Murtanto (Dinasti Publisher, 2025)
The objective aims to analyze the effect of green finance, green energy, and ESG performance on carbon neutrality firms registered on the IDX throughout the timeframe 2020–2022. The research sample consists of companies in the energy sector, transportation, industry, and basic materials that produce high intensive energy that were listed on the Indonesia Stock Exchange during the specified period and had published audited annual reports. Using a purposive sampling method, 26 companies were selected as samples, resulting in a total of 78 observational data points. This research employs panel regression analysis, utilizing annual and ESG-related reports. The results show that green energy and ESG Performance have a significant positive effect on carbon neutrality. Meanwhile, green finance does not have a significant effect on carbon neutrality.